In-vitro optimization and active-site mutagenesis of CYP105D18 peroxygenase enhance the production of indigo - Pardhe, Bashu Dev; Park, Hyun A.; Paudel, Prakash; Jeong, Jaeho; Oh, Tae Jin; Choi, Kwon Young; Ahn, Jungoh (Enzyme and Microbial Technology, 2025)
Practical implementation of efficient biocatalysts for large-scale production of indigo remains challenging. Microbial cytochrome P450s may be useful for indigo production, but this has been rarely reported. We discovered that CYP105D18 catalysed H2O2-mediated C-3 hydroxylation of indole to synthesize indigo. A cell-free lysate from Escherichia coli containing CYP105D18 peroxygenase obtained after cell disruption was optimized for in vitro reaction. Next, 250 µM hydroxylamine was added to the cell-free lysate to inhibit other H2O2-utilizing enzymes that interfere with the CYP105D18 function. Furthermore, the active-site residues of CYP105D18, namely L87, A235, A282, and I386, involved in indole binding were mutated. L87F resulted in an approximately 12-fold increase in CYP105D18 activity. The catalytic efficiencies of the wild-type and L87F mutant were 0.01 and 0.12 mM−1min−1, respectively. Fed-batch fermentation using enriched autoinduction medium was used for higher production of E. coli cells containing CYP105D18 peroxygenase. The Cell-free lysate of disrupted cells yielded 710 mg/L of indigo in 20 min. This represents a simple enzymatic approach for indigo biosynthesis using cell-free lysate of E. coli overexpressing CYP105D18, H2O2, and catalase inhibitor without the need for multi enzyme systems and expensive cofactors. This single-enzyme system, used in a rapid process for indigo formation, could serve as an efficient approach for commercial bio-indigo production.
Keywords: Autoinduction; Autoinduction medium; Catalase inhibitor; Cell-free; Cell-free lysate; Cyp105d18; Enzyme systems; In-vitro; Indigo; Lysates; Catalytic Domain; Cytochrome P-450 Enzyme System; Escherichia coli; Escherichia coli Proteins; Hydrogen Peroxide; Hydroxylation; Indigo Carmine; Indoles; Mutagenesis, Site-Directed; Recombinant Proteins; Autoinduction medium; Catalase inhibitor; Cell-free lysate; CYP105D18; Indigo